2020
DOI: 10.3991/ijet.v15i13.14665
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Commercialization of the Results of the “Multidisciplinary Mobile Computer Classroom Based on Raspberry Pi” Project

Abstract: This paper describes the developed technology for using the Raspberry Pi micro-computer to teach practical skills on computer networks and operating systems. The effectiveness of acquiring skills using the proposed technology is due to the fact that it allows organizing the workshops with personal support with the necessary special tools. The paper presents a largely implemented project on an initiative basis, preceding the work on commercialization of the described results. In the present work a full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…One significant development trend of science since the 20th century is its integration with technology and mutual penetration of science, technology, and society, i.e., the transformation from single disciplinary knowledge production mode into interdisciplinary interactive mode [1][2][3][4][5]. Interdisciplinary research has been advanced rapidly and its prosperity also reflects the basic situation for the development of science and technology in modern times, such as complicated scientific structure, organic scientific activity and softened ideal objectives [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…One significant development trend of science since the 20th century is its integration with technology and mutual penetration of science, technology, and society, i.e., the transformation from single disciplinary knowledge production mode into interdisciplinary interactive mode [1][2][3][4][5]. Interdisciplinary research has been advanced rapidly and its prosperity also reflects the basic situation for the development of science and technology in modern times, such as complicated scientific structure, organic scientific activity and softened ideal objectives [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of single board architectures integrating sensors technologies and their applications has led to different tutorials, overviews, reviews and surveys papers being reported in the literature, included on-line publications, white papers, webinars and different aspects, topics and points of view: SoC technologies, process capacity, characteristics, power and number of I/O, in terms of cost, control flexibility, among others. In this sense SBAs and ISTs for visual sensor networks are revised and analyzed in [ 87 , 88 ], transport technologies and related applications in [ 89 , 90 ] including tracking, monitoring and lighting in [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ], SBAs and ISTs for smart cities applications in [ 99 , 100 ], education and research projects in [ 101 , 102 , 103 , 104 , 105 ], medical devices in [ 106 , 107 , 108 ], smart and advanced sensors in [ 109 , 110 , 111 , 112 , 113 ], including wireless sensors [ 114 ], IoT applications in [ 115 , 116 , 117 , 118 ], smart home in [ 119 , 120 , 121 , 122 ], energy in [ 123 , 124 , 125 ], engineering education in [ 126 , 127 , 128 ], Hybrid Electric Vehicle (HEV), Fuel Cell Electric Vehicles (FCEV) and Plug-in-Hybrid Electric Vehicle (PHEV) in [ 129 ,…”
Section: Introductionmentioning
confidence: 99%
“…Raspberry Pi типті микрокомпьютерлерін пайдаланып әзірленген әр түрлі жобалар авторлардың [1][2] жұмыстарында берілген болатын. Осы зерттеу жұмыстарында аталған құрылғыны тиімді қолдану мысалдары келтірілді.…”
unclassified